1992
DOI: 10.1002/hlca.19920750616
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structure of [4.5.5.5]Fenestranes ( = tetracyclo[5.4.1.04, 12.09, 12]dodecanes)

Abstract: The preparation and the X-ray structure analysis of ci.~,truns,cis,cis-lO-hydroxy-[4.5.5.5]fenestrane-lmethanol (8b) is reported. The measured bond angles and bond lengths of the central C(C), fragment are better reproduced by calculations with the AM1 than by the MNDO method.Introduction. -The tetracyclic fenestranes, where four rings share a central C-atom, are a unique class of hydrocarbons, because two opposite bond angles in the central C(C), substructure are consistently larger than 109" 28'. This type o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

1996
1996
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 20 publications
0
8
0
2
Order By: Relevance
“…trans ‐Isomere sind vielversprechender: Die berechneten Winkel α und β sind jeweils 118° und 126° für t , c , c , c‐ [5.5.5.5]Fenestran (Abbildung 9 c) und jeweils 130° und 137° für c , t , c , t ‐[5.5.5.5]Fenestran (Abbildung 9 d). 17c, 21 In [4.5.5.5]Fenestr‐8‐en wurden Brückenkopf‐Doppelbindungen, kleinere Ringe und trans ‐Beziehung in einer Verbindung kombiniert; α wäre hier 138° und β 131° (Abbildung 10 a). 17c Sterisch anspruchsvolle Substituenten in Brückenkopfpositionen, wie in 1,6‐Dimethyl‐[4.5.5.5]fenestr‐8‐en (Abbildung 10 b), erhöhen die berechneten Werte geringfügig.…”
Section: Definition Der Fenestrane Ihre Nomenklatur Und Die Binduunclassified
See 1 more Smart Citation
“…trans ‐Isomere sind vielversprechender: Die berechneten Winkel α und β sind jeweils 118° und 126° für t , c , c , c‐ [5.5.5.5]Fenestran (Abbildung 9 c) und jeweils 130° und 137° für c , t , c , t ‐[5.5.5.5]Fenestran (Abbildung 9 d). 17c, 21 In [4.5.5.5]Fenestr‐8‐en wurden Brückenkopf‐Doppelbindungen, kleinere Ringe und trans ‐Beziehung in einer Verbindung kombiniert; α wäre hier 138° und β 131° (Abbildung 10 a). 17c Sterisch anspruchsvolle Substituenten in Brückenkopfpositionen, wie in 1,6‐Dimethyl‐[4.5.5.5]fenestr‐8‐en (Abbildung 10 b), erhöhen die berechneten Werte geringfügig.…”
Section: Definition Der Fenestrane Ihre Nomenklatur Und Die Binduunclassified
“…Dennoch ist die Synthese von Fenestranen nicht unkompliziert, und bis heute wurde kein Fenestran erhalten, in dem beide Winkel größer als 130° sind. Die Beispiele mit den größten Winkeln sind in Abbildung 18 gezeigt: das c , c , t , c ‐[4.5.5.5]Fenestran 87 (RSA: 132.4°, 119.5°),57b das c , c , t , c ‐[4.5.5.5]Fenestran 44 b (RSA: 131.1°, 120.2)58a und das c , c , c , c ‐[4.4.4.5]Fenestran 88 (RSA: 128°, 129°) 71. Die Verbindung, die alle vier Bedingungen für die Planarisierung erfüllt, das 1,7‐Dimethyl‐ c , c , t , c ‐[4.5.5.5]fenestr‐9‐en 89 , sollte die größten Winkel haben (DFT: 140°, 132°) 17a.…”
Section: Zusammenfassung Und Ausblickunclassified
“…The enlargement of the bond angle C2--C1---C11 to 124.3 ° is also observed. Compared with the average bond angles of 126 (4) and 127 (6) ° determined from 19 trans-bicyclo[3.3.0]octane subunits retrieved from the Cambridge Structural Database (Allen & Kennard, 1993), the C4--C12---C9 bridgehead angle of 134.9 (2) ° in (3b) is significantly larger (Hirschi et al, 1992).…”
Section: Introductionmentioning
confidence: 78%
“…In our systematic search for fenestranes with strong planarizing distortions, it was found that the simultaneous incorporation of trans-bicyclo[3.3.0]octane subunits and bridgehead substituents led to enlarged opposite bond angles at the central C atom. In order to verify this computational result and to compare the structure of (3b) with that of the structurally similar cis, trans,cis, cis-[4.5.5.5]fenestranediol, (5) (Hirschi, Luef, Gerber & Keese, 1992), the known compound (2a) was prepared from (1) by a new route, transformed via (2b) into (3a) by a previously published method (Grieco, Brandes, McCann & Clark, 1989) and oxidized with Jones reagent (acetone, 298 K) to compound (3b).…”
Section: Introductionmentioning
confidence: 99%
“…For methods to enhance the planarizing distortions in the central C(C) 4 substructure, see: Luef & Keese (1993). For an analysis of the bond angles and other details concerning trans-fused bicyclo[3.3.0]octanes, see: Hirschi et al (1992). For information concerning the Pauson-Khand reaction, see: ; Khand, Knox, Pauson, Watts & Foreman (1973).…”
Section: Related Literaturementioning
confidence: 99%